2006
DOI: 10.1002/eji.200636110
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive components of Ascaris suum down‐regulate expression of costimulatory molecules and function of antigen‐presenting cells via an IL‐10‐mediated mechanism

Abstract: High-molecular-weight components (PI) of Ascaris suum suppress both cell-mediated and humoral responses against ovalbumin (OVA) via an IL-4/IL-10-dependent mechanism. The aim of this work was to investigate the effect of PI on the ability of APC to activate T cells and the role of IL-10 in this process. Flow cytometry analyses of MHC class II, CD80, CD86 and CD40 molecules on LN cells from mice immunized with OVA or OVA+PI showed that PI inhibits expression of these molecules on unfractionated cells and on pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
0
27
0
7
Order By: Relevance
“…Surprisingly, the A. suum extract decreased IL-10 levels to below detection limits in naïve rats as well as in both rats and mice subjected to ZYA. This is intriguing, since high-molecular-weight components of this extract were shown to downregulate the presentation of antigens by dendritic cells via an IL-10-dependent mechanism (28). The fact that we measured IL-10 levels in vivo, whereas the results from reference 28 were obtained in vitro, may explain this discrepancy.…”
Section: Vol 76 2008 Helminth Protection In Immune Arthritis 2743mentioning
confidence: 72%
See 1 more Smart Citation
“…Surprisingly, the A. suum extract decreased IL-10 levels to below detection limits in naïve rats as well as in both rats and mice subjected to ZYA. This is intriguing, since high-molecular-weight components of this extract were shown to downregulate the presentation of antigens by dendritic cells via an IL-10-dependent mechanism (28). The fact that we measured IL-10 levels in vivo, whereas the results from reference 28 were obtained in vitro, may explain this discrepancy.…”
Section: Vol 76 2008 Helminth Protection In Immune Arthritis 2743mentioning
confidence: 72%
“…Using mice sensitized to ovalbumin, it has been demonstrated that the A. suum crude extract, prepared as used in the present study, or its affinitypurified high-molecular-weight components are able to downmodulate the antigen-processing ability of dendritic cells (28). Results represent means Ϯ SEM (n ϭ 6 animals for each group).…”
Section: Discussionmentioning
confidence: 86%
“…A. suum re- 12 leases potent immunosuppressive molecules that interfere with antigen presentation of dendritic cells [60] . The purified proteins maintain their ability to inhibit T-cell-dependent antibody production and to suppress both Th1 and Th2 responses through modulation of IL-4 and IL-10 [61] .…”
Section: Immune Responses To Ascarismentioning
confidence: 99%
“…It has been shown that PI downregulates the expression of costimulatory agents (CD40, CD80 and CD86) and major histocompatibility complex II molecules on the surface of dendritic cells and, consequently, reduces the antigen-presenting function of these cells. This effect was mediated by IL-10 16 . IFN-γ and IL-10 have opposite effects on immune system activation 10 .…”
Section: Figurementioning
confidence: 88%